2016
DOI: 10.1103/physreve.94.032215
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic self-oscillations and aging transition in a network of synaptically coupled quadratic integrate-and-fire neurons

Abstract: We analyze the dynamics of a large network of coupled quadratic integrate-and-fire neurons, which represent the canonical model for class I neurons near the spiking threshold. The network is heterogeneous in that it includes both inherently spiking and excitable neurons. The coupling is global via synapses that take into account the finite width of synaptic pulses. Using a recently developed reduction method based on the Lorentzian ansatz, we derive a closed system of equations for the neuron's firing rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…As proved recently [38], NFMs with time-scale separation display a rich variety of robust spatio-temporal patterns, which may also be supported by our model. Also, recent work has been done to extend the local firing rate equations derived in [28] to include synaptic kinetics [39][40][41][42] or fixed delays [43]. These studies all show that time delays due to synaptic processing generally lead to the emergence of self-sustained oscillations due to collective synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…As proved recently [38], NFMs with time-scale separation display a rich variety of robust spatio-temporal patterns, which may also be supported by our model. Also, recent work has been done to extend the local firing rate equations derived in [28] to include synaptic kinetics [39][40][41][42] or fixed delays [43]. These studies all show that time delays due to synaptic processing generally lead to the emergence of self-sustained oscillations due to collective synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…These regimes could be well traversed via transient inputs, as depicted in Figure 4B. Driving the microscopic model given by (2) and (20)(21)(22)(23) with the same transient inputs, we found that the spiking dynamics were still attracted to the low-dimensional manifold described by the macroscopic system. This shows, that even with τ A = 10τ , the condition τ A τ is sufficiently satisfied for the macroscopic description of the population bursting dynamics to be valid.…”
Section: Ivb Effects Of Sfamentioning
confidence: 79%
“…Forη, the parameter range in which the limit cycle exists corresponds to most of the cells in the population being in an excitable regime and has been reported for a number of models using QIF neurons (e.g. 15,22,23 ). Within this range, the inter-burst period can be varied from 13τ up to 105τ via changes in α andη (see Figure 3B).…”
Section: Iiic Limit Cycle Characteristicsmentioning
confidence: 85%
“…Even though the Montbrió model is only a single-population model, it has been shown 620 to have a rich dynamic profile with oscillatory and even bi-stable regimes [38,47] while the frequency of the oscillatory forcing was chosen as ω = π 20 . As shown in Figure 635 3, we were able to replicate the above described model behavior.…”
Section: Montbrió Model 619mentioning
confidence: 99%
“…Even though the Montbrió model is only a single-population model, it has been shown to have a rich dynamic profile with oscillatory and even bi-stable regimes [38,47]. To investigate the response of the model to non-stationary inputs, Montbrió et al initialized the model in a bi-stable dynamic regime and applied (1) constant and (2) sinusoidal extrinsic forcing within a short time-window.…”
Section: Montbrió Modelmentioning
confidence: 99%